KEPUTUSAN INVESTASI PEMILIK MODAL HOTEL BERBINTANG (Studi Kasus pada PT.”X” Pemilik Hotel “Y” Jember) - Chandra Setiawan Tri Yuwono (Jurnal Ilmiah Akuntansi Indonesia, 2016)
Based on the growth rate of the hotel that indicated the level actual disbursement of credit showed a positive increase. The compositional in the Gross Regional Domestic Product (GRDP) shows an arrangement of the hotel GRDP lower than the Wholesale Retail GRDP, as well as the Restaurant GRDP. The occupancy rate of tourists, both foreign and domestic showed a significant decrease each year. With that data PT. "X" made the decision to investment at the hotel "Y" with category four-star.This raises a question how the rational reasons PT. "X" to make investment decisions at the hotel "Y" with a four-star category. This study uses qualitative research methods with intensive interviews to the management of PT. "X" and do the triangulation analysis to data obtained. The results of this study concluded that the PT. "X" is a type of reasonable investor according to Lin (2015) and according Natapura (2009) concluded that PT. "X" is a type of rational investors.Keywords: Behavioral Finance, Investor Type, Investmen